2021
DOI: 10.1186/s12864-021-07991-7
|View full text |Cite
|
Sign up to set email alerts
|

Morphological, physiological, and transcriptional responses to low nitrogen stress in Populus deltoides Marsh. clones with contrasting nitrogen use efficiency

Abstract: Background Nitrogen (N) is one of the main factors limiting the wood yield in poplar cultivation. Understanding the molecular mechanism of N utilization could play a guiding role in improving the nitrogen use efficiency (NUE) of poplar. Results In this study, three N-efficient genotypes (A1-A3) and three N-inefficient genotypes (C1-C3) of Populus deltoides were cultured under low N stress (5 μM NH4NO3) and normal N supply (750 μM NH4NO3). The dry m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 75 publications
0
6
0
Order By: Relevance
“…S5 ). Previous studies have shown that gene expression levels [ 5 , 40 , 41 ] and enzyme activities associated with nitrogen metabolism differ significantly at different N levels [ 27 , 42 , 43 ]. We focused on examining the differences gene expression involved in major pathways of N metabolism under fertilization conditions (Fig.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…S5 ). Previous studies have shown that gene expression levels [ 5 , 40 , 41 ] and enzyme activities associated with nitrogen metabolism differ significantly at different N levels [ 27 , 42 , 43 ]. We focused on examining the differences gene expression involved in major pathways of N metabolism under fertilization conditions (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…The hub genes of this module include four genes directly or indirectly involved in nitrogen metabolism and two NAC transcription factors ( PtrNAC025 and PtrNAC12 ). Previously, Chen et al [ 5 ] constructed a four-layer transcriptional regulatory network (TRN) for poplar wood formation. This network, with PtrSND1 as the top-level regulatory factor and PtrMYB74 and PtrMYB21 as second-level regulatory factors, regulate the expression of 17 target genes and their downstream genes involved in secondary cell wall biosynthesis during wood formation [ 21 , 46 , 47 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Woody bioenergy plants are expected to contribute an estimated 300 million tonnes of dry biomass in 2030 (Downing et al, 2011). Poplar ( Populus ) has the advantage of rapid growth in woody plants and is widely planted worldwide and in China (Chen et al, 2021; Sun et al, 2019). Hybrid poplars have higher lignin and cellulose contents than other major bioenergy crops (Table 1).…”
Section: Introductionmentioning
confidence: 99%
“…Hybrid poplars have higher lignin and cellulose contents than other major bioenergy crops (Table 1). Most poplar plantations are planted in nitrogen-poor areas, which predisposes them to low productivity (Chen et al, 2020(Chen et al, , 2021Song et al, 2020). Therefore, nitrogen deficiency has become a major factor limiting the sustainable development of poplar productivity.…”
Section: Introductionmentioning
confidence: 99%